Electronic media : then, now, and later - Medoff, Norman J. (Focal Press, 2011)
Electronic Media connects the traditional world of broadcasting with the contemporary universe of digital electronic media. It provides a synopsis of the beginnings of electronic media in broadcasting, and the subsequent advancements into digital media. Underlying the structure of the book is a ""See It Then, See It Now, See It Later"" approach that focuses on how past innovations lay the groundwork for changing trends in technology, providing the opportunity and demand for change in both broadcasting and digital media. FYI and Zoom-In boxes point to further information, tying together the imm